Understanding how trainee teachers engage with prior everyday knowledge and experience associated with biological concepts during integrated natural science education 5-7 : a case study - Enghono, Albertina Magano (Rhodes University, Faculty of Education, Department of Education, 2014)
Since the Namibian independence in 1990, the education system has undergone some major revamping which involved the adoption of social constructivist perspectives in the teaching and learning of sciences. This learning theory acknowledges learners' background prior knowledge as valuable tools in the effective construction of science concepts during lessons. A corollary is that the socio-cultural circumstances of learners might negatively influence the way learners construct new knowledge in the science classroom if they are not taken into consideration. This study was thus prompted by the need to understand how trainee science teachers engage with prior everyday knowledge and experiences, so as to enhance the conceptual development of biological concepts. The study was qualitative and it was underpinned by an interpretive paradigm with some elements of action research. Science trainee teachers at Katima Mulilo, Unam Campus were used as research participants. The techniques used to gather data included document analysis, brainstorming, observation, audio-visual, microteaching and semi-structured interviews. The results of this study showed that the changes that occurred during microteaching practices of the four trainee teachers involved in the study reflected their professional development in this approach. However, it emerged that prior everyday knowledge can be both a barrier and enabler to the construction of meaningful teaching and learning; hence its oversight may lead to instructional failures. The findings also indicated that selected platforms are essential to enable trainee teachers to incorporate prior everyday knowledge and experiences into the teaching of Western science. However, larger scale study should be conducted in order to deepen the understanding of the topic.
Keywords: Biology teachers -- Training of -- Namibia -- Case studies; Teacher educators -- Training of -- Case studies; Teachers -- Training of -- Namibia -- Case studies; Education -- Namibia -- Case studies; Prior learning -- Namibia